Drug Related Problems Identified by Clinical Pharmacist in a Tertiary Care Hospital in South India: An Observational Study - Kumar, Maddela Vinay; Pasha, Mohammad Mohasin; Varshith, Gandla; Pravalika, Borampeta; Shameela, Mudugu (Journal of Pharmacy Practice and Community Medicine)
Introduction: Drug related problems (DRP) negatively impact the quality of life of the patient and increase the burden of illnesses in terms of economic and social factors. In order to reduce medication errors, adverse reactions, and length of stay, pharmacy services must identify and classify potential DRPs. The goals of this study are thus to identify DRPs by reviewing medical orders (MOs) given to each patient, and to analyses DRPs using PCNE classification. Materials and Methods: This study was conducted in eight medical wards in a multispeciality hospital using prospective observational cohort research. Pharmaceutical Care Network Europe’s version 9.1 classification system (version 9.1) was used to identify and classify potential DRPs based on the patients’ medical orders. Results: A total of 394 patients were admitted to the hospital wards for treatment of a variety of clinical conditions during the study period. From the total cohort, 190 (48%) medical orders were detected with DRP. A total of 324 DRPs were detected and classified among 190 patients using PCNE 9.1. Among them, drug-drug interactions (16.3%) account for the highest prevalence followed by incomplete drug treatment (15.4%), documentation error (12.3%), monitoring errors (13.8%). Conclusion: The current study emphasizes the importance of reporting DRPs to patients in order to provide better health care and advocates the significance of clinical pharmacists in pharmaceutical patient care.
Keywords: Drug related problems; Medication errors; PCNE classification; Clinical pharmacists; Pharmaceutical patient